Cracking the Financing Gap: How Informal Traders in Zimbabwe are Bridging the Banking Divide - Mutanda, Bronson (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
In Zimbabwe, informal traders face significant barriers in accessing formal financial services, hindering their ability to grow and sustain their businesses. However, these traders are finding innovative ways to bridge the banking gap by leveraging alternative financial services. The paper investigates alternative financial services leveraged by informal traders in Zimbabwe. Quantitative results reveal that majority of informal traders in Zimbabwe are financially excluded and rely heavily on informal financial services such as mukando/revolving funds, chimbadzo/interest bearing informal loans, personal savings, trade credit, business angels, burial society group loans and loans from friends and relatives. Quantitative results further revealed that informal traders in Zimbabwe leverage private strong rooms, mukando/revolving funds and cryptocurrencies for savings and investments. Furthermore, qualitative results revealed that informal traders in Zimbabwe also save and invest through the gaba scheme and informal deposit taking financial institutions. Based on research findings, the study concludes that informal traders in Zimbabwe are financially excluded and rely on informal financial services. This underscores the necessity for a collaborative and multi-faceted approach among policymakers, stakeholders, and industry experts to effectively integrate the informal sector into the formal financial system. The research recommends the introduction of customised financial products, simplification of loan and bank account application procedures, introduction of AI augmented bank accounts, consultative meetings between policy makers and representatives of informal traders and introduction of mobile banking vehicles with automated teller machines.